Developmental Control and Plasticity of Fruit and Seed Dimorphism in Aethionema arabicum . Issue 3 (4th October 2016) - Lenser, Teresa; Graeber, Kai; Cevik, Özge Selin; Adigüzel, Nezaket; Dönmez, Ali A.; Grosche, Christopher; Kettermann, Marcel; Mayland-Quellhorst, Sara; Mérai, Zsuzsanna; Mohammadin, Setareh; Nguyen, Thu-Phuong; Rümpler, Florian; et al.
Abstract : Aethionema arabicum produces two different fruit and seed types with distinct anatomical, biomechanical, and physiological properties. Abstract: Understanding how plants cope with changing habitats is a timely and important topic in plant research. Phenotypic plasticity describes the capability of a genotype to produce different phenotypes when exposed to different environmental conditions. In contrast, the constant production of a set of distinct phenotypes by one genotype mediates bet hedging, a strategy that reduces the temporal variance in fitness at the expense of a lowered arithmetic mean fitness. Both phenomena are thought to represent important adaptation strategies to unstable environments. However, little is known about the underlying mechanisms of these phenomena, partly due to the lack of suitable model systems. We used phylogenetic and comparative analyses of fruit and seed anatomy, biomechanics, physiology, and environmental responses to study fruit and seed heteromorphism, a typical morphological basis of a bet-hedging strategy of plants, in the annual Brassicaceae species Aethionema arabicum . Our results indicate that heteromorphism evolved twice within the Aethionemeae, including once for the monophyletic annual Aethionema clade. The dimorphism of Ae. arabicum is associated with several anatomic, biomechanical, gene expression, and physiological differences between the fruit and seed morphs. However, fruit ratios and numbers change in response to different environmental conditions. Therefore, the life-history strategy of Ae. arabicum appears to be a blend of bet hedging and plasticity. Together with the available genomic resources, our results pave the way to use this species in future studies intended to unravel the molecular control of heteromorphism and plasticity.